2018
DOI: 10.1002/ecs2.2400
|View full text |Cite
|
Sign up to set email alerts
|

Restoring historical forest conditions in a diverse inland Pacific Northwest landscape

Abstract: A major goal of managers in fire-prone forests is restoring historical structure and composition to promote resilience to future drought and disturbance. To accomplish this goal, managers require information about reference conditions in different forest types, as well as tools to determine which individual trees to retain or remove to approximate those reference conditions. We used dendroecological reconstructions and General Land Office records to quantify historical forest structure and composition within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 87 publications
(86 reference statements)
2
22
0
Order By: Relevance
“…Furthermore, grand fir is also the most drought-tolerant fir in the Pacific Northwest (Howard and Aleksoff 2000), and it can establish and survive on a range of sites from moist to warm and moderately dry (Lillybridge et al 1995). In the Blue Mountains, as well as in the neighboring Ochoco and Cascade Mountains to the west, infilling of late-seral species (grand fir and, to a lesser extent, Douglas-fir) in formerly ponderosa pine-dominated sites has been demonstrated beginning around the 1880s, likely as a result of widespread fire suppression (Merschel et al 2014, Johnston et al 2018. Grand fir is moderately fire resistant once it reaches maturity (Howard and Aleksoff 2000) and generally only dominates in areas where fire has been excluded (Habeck and Mutch 1973).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, grand fir is also the most drought-tolerant fir in the Pacific Northwest (Howard and Aleksoff 2000), and it can establish and survive on a range of sites from moist to warm and moderately dry (Lillybridge et al 1995). In the Blue Mountains, as well as in the neighboring Ochoco and Cascade Mountains to the west, infilling of late-seral species (grand fir and, to a lesser extent, Douglas-fir) in formerly ponderosa pine-dominated sites has been demonstrated beginning around the 1880s, likely as a result of widespread fire suppression (Merschel et al 2014, Johnston et al 2018. Grand fir is moderately fire resistant once it reaches maturity (Howard and Aleksoff 2000) and generally only dominates in areas where fire has been excluded (Habeck and Mutch 1973).…”
Section: Discussionmentioning
confidence: 99%
“…This has increased the continuity of horizontal and vertical fuels thereby causing higher overstory mortality when wildfires do occur (Agee 1998, Agee andSkinner 2005). Fire suppression has also altered forest composition by facilitating the establishment of fire-intolerant tree species such as grand fir (Abies grandis; Larson and Churchill 2012, Merschel et al 2014, Johnston et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three PDE methods did not show a discrepancy in density estimates between 2nn only and 4nn only sampling (see Levine Appendix S1). In an independent study, a comparison of PDEs found the Voronoi density estimate (Williams and Baker 2011) for the Blue Mountains of Oregon "unreliable" and more than twice that independently estimated by either Cottam or Morisita estimators alone (Johnston et al 2018).…”
Section: New Simulationsmentioning
confidence: 97%
“…In addition, the 4nn and 2nn sampling have different responses to nonrandom or heterogeneous dispersion (Cogbill et al 2018). In an independent study, a comparison of PDEs found the Voronoi density estimate (Williams and Baker 2011) for the Blue Mountains of Oregon "unreliable" and more than twice that independently estimated by either Cottam or Morisita estimators alone (Johnston et al 2018). The mixing of disparate densities based on MND scaling confounds the calculation of MVA.…”
Section: New Simulationsmentioning
confidence: 99%